One-week flipped workshop on heat integration - Lewin,DR; Shah,N; Barzilai,A (2025)
This paper describes the first implementation of a flipped, one-week workshop on heat integration that was taught in Spring 2024 to the 3rd Year cohort of 138 students in Chemical Engineering at Imperial College, London. The “flipped” workshop consisted of three online lessons that cover the core materials on pinch design of heat exchanger networks, which the students were required to complete ahead of each of the corresponding three face-to-face class meetings, which focused on problem-solving exercises largely carried out by the students themselves. The paper describes the teaching methodology applied, presents and analyses the results of a survey conducted to assess the students’ perceptions and degree of satisfaction with the workshop. Learning outcomes relevant to the workshop topic, that is, the ability to design and optimize heat exchanger networks in realistic plant-wide settings, are also presented and compared to those of previous years. The main conclusion is that the short workshop format can successfully achieve the learning objectives, even for relatively large class sizes. Evidently, this workshop can be taught effectively in this concentrated form provided that the workshop participants are given access to the online lessons in advance of the class exercises.